Briefe an Freunde - Luxemburg, Rosa; Kautsky, Luise; Kautsky, Benedikt (Hamburg : Europäische Verlagsanstalt, 1950)
Bevat brief van Rosa Luxemburg en Karl Liebknecht aan Camille Huysmans
Bibliotheek Camille Huysmans
Duits
Monografie
Keywords: Luxemburg, Rosa; Huysmans, Camille